Can we learn anything from health care in the United States?. Issue 9 (19th May 2014) - Anstey, Matthew H R; Elshaug, Adam G; Russell, Lesley M; Wells, Susan
Summary: Some aspects of health care in the United States would be beneficial to Australia and New Zealand, but others should be avoided. Positive aspects, which should be emulated, include: ➢ health care reform that is focused on the continuum of care and patient‐centred care ➢ trials of new models to organise, deliver and pay for health care services, where quality of care is rewarded over quantity of services ➢ an integral view of, and strong support for, health services research as a means of evaluating reforms aimed at improving patient outcomes and systems‐level efficiencies ➢ physician engagement in reforms — for example, participating in the Choosing Wisely initiative, and trialling and implementing new payment models that are not fee‐for‐service. Negative aspects, which should be avoided, include: ➢ increasingly fragmented provider and financing structures (funding provided by state and federal governments, private insurance and out‐of‐pocket costs) that cause frustration in terms of access and care coordination and increase administrative waste ➢ an overemphasis on technological solutions, with insufficient acknowledgment of the importance of addressing value in health care ➢ a focus on hospital and doctor‐based health care rather than environmental and social inputs into health.